Selective bronchial occlusion for the prevention of pneumothorax after transbronchial lung cryobiopsy in a pulmonary alveolar proteinosis patient: a case report - Wu, Hua-Man; Wen, You-Li; He, Xiao-Yu; Deng, Zhi-Ping (Frontiers in Medicine, 2023)
The diagnosis of pulmonary alveolar proteinosis (PAP) is based on biopsies. Compared with other methods of taking biopsies, transbronchial lung cryobiopsy (TBLC) has a higher diagnostic rate and the likelihood of pneumothorax. Selective bronchial occlusion (SBO) is an effective technique for treating intractable pneumothorax. However, there are no data available about SBO for the prevention of pneumothorax after TBLC in a PAP patient. A 49-year-old man complained of recurrent cough and tachypnea, and his symptoms did not fully resolve until the diagnosis was confirmed, and he was treated with whole lung lavage. Our patient was ultimately diagnosed with PAP by TBLC but not multiple tests for the bronchoalveolar lavage fluid (BALF). The patient was discharged quickly after whole lung lavage due to the fact that he did not develop pneumothorax under SBO. This case illustrates that TBLC is a supplementary examination for PAP, especially for those in whom BALF results fail to confirm a diagnosis. Moreover, our report highlights that SBO is necessary to effectively prevent pneumothorax during and after multiple TBLCs in PAP patients.